2006
DOI: 10.1002/adma.200501077
|View full text |Cite
|
Sign up to set email alerts
|

Conformally Back‐Filled, Non‐close‐packed Inverse‐Opal Photonic Crystals

Abstract: Photonic crystals (PCs) offer far greater control over the generation and propagation of light than any other material structures. [1,2] Their defining characteristics, omnidirectional and directional photonic bandgaps (PBGs), can be manipulated to enable effects such as low losses in optical circuits and control of spontaneous emission. PCs are also creating much excitement because of their ability to form flat bands, yielding phenomena such as slow light and negative refraction. [3,4] The infiltration and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 23 publications
1
50
0
Order By: Relevance
“…Unlike CVD, ALD is self-limiting by keeping the precursors separate, enabling ultrahigh-precision control over the deposition and providing superior film conformity and uniformity even for complex structures with ultrahigh aspect ratios [15][16][17][18][19]. Thus, ALD has been used as a way of infiltrating NCC templates to generate inverse opals [19][20][21][22][23][24][25][26]. Our previous studies [27,28] demonstrated that ALD can be used to significantly reinforce films composed of randomly packed polydisperse nanoparticles.…”
Section: Introductionmentioning
confidence: 95%
“…Unlike CVD, ALD is self-limiting by keeping the precursors separate, enabling ultrahigh-precision control over the deposition and providing superior film conformity and uniformity even for complex structures with ultrahigh aspect ratios [15][16][17][18][19]. Thus, ALD has been used as a way of infiltrating NCC templates to generate inverse opals [19][20][21][22][23][24][25][26]. Our previous studies [27,28] demonstrated that ALD can be used to significantly reinforce films composed of randomly packed polydisperse nanoparticles.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, Míguez et al and King et al reported techniques to partially overcome this limitation by using extended heavy presintering of the opal template to increase the necking (or overlap) between neighboring spheres, thus increasing the inverse-pore diameter and allowing a higher degree of backfilling. [18,19] Although this technique can lead to enhanced properties, heavy presintering is unable to provide the nanometer-scale precision and control required to produce high-quality inverse opals. Additionally, it is incompatible with many template materials and structures.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of features is not surprising in any case as a 'dense' silica layer is generally observed at the film surface when using the vapor pressure of TEOS to deliver the silica to the preformed template [38,49]. Previously, King et al used ion beam milling to remove a capping TiO 2 layer to expose colloid templated pores [52]. In attempts to expose the pore structure of these materials, similar ion beam milling was used.…”
Section: Impact Of Copolymer Chemistrymentioning
confidence: 97%